UJI SITOTOKSISITAS FRAKSI n-HEKSANA EKSTRAK ETANOL HERBA ALFALFA (Medicago Sativa L.) PADA SEL T47D DAN SEL HeLa SERTA IDENTIFIKASI KANDUNGAN SENYAWA KIMIANYA - sri susilowati; anggun claresa; ibrahim arifin (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2012)
ABSTRACTBreast and cervical cancers were the high prevalency, both in the world and Indonesia. This study aimed to determine the cytotoxic activities and its potentcy of n-hexane fraction of ethanol extract alfalfa herb (Medicago sativa L.) in T47D cells and HeLa cells, also identificated its chemical compounds.Extraction was done using ethanol by soxhletation method and then followed fractionation with n-hexane. Cytotoxic assay to get the value of IC50 was carried out by using MTT assay with a series of concentration of fraction 62,5; 125; 250; 500; 1000 μg/ ml. The cytotoxic activities was determined with viability cells from absorbance ELISA reader. Identification of chemical compounds of n-hexane fraction of ethanol extract alfalfa herb was done using chemical reactan and paper chromatography and then was evaluated qualitatively.The results showed that the n-hexane fraction of ethanol extract of alfalfa herb had cytotoxic activities in T47D cells and HeLa cells. The IC50 values were 523,9 μg/ml in T47D cells and 503,5 μg/ml in HeLa cells. The chemical compounds of n-hexane fraction of ethanol extract of alfalfa herb were coumarin and flavonoid.Key words : cytotoxic assay, n-hexane fraction of ethanol extract of herb alfalfa, Medicago sativa L., T47D cells, HeLa cells, flavonoid, coumarin